Electrochemical Ecthing Of Quenched Sac305 Solders - Ramlee, Nor Azmira Salleh @ (Universiti Sains Malaysia, 2017)
The effect of cooling methods such as oven cooling, air cooling, water quenching and ice quenching of SAC305 solder on phase and microstructure of intermetallic compounds (IMC) at interface and solder bulk were investigated. Phases present in SAC305 solder with different cooling methods were analysed by X-ray diffraction. Then, the microstructures of IMC at interface and bulk solder of SAC305 was investigated by chemical etching and selective electrochemical etching method. The potential applied in the electrochemical etching was -0.35 V s-1. Typical phases of SAC305 are β-Sn, Ag3Sn, and Cu6Sn5. The formation of α-Sn was observed as the cooling is done using ice. For microstructure analysis of IMC at interface and bulk solder, observation on sample etched using chemical etching showed good orientation on the SAC305 solder with different depth of IMC and dissolved IMC. Hence, by electrochemical etching, it revealed only the important phase and only Sn phase was etched away when the potential bias was applied. The application of selective electrochemical etching method revealed the IMC microstructures clearly. The IMC layer of SAC305 cooled by oven have highest IMC layer, followed by SAC305 solder cooled by air, water and ice. The highest cooling rate will increased the time for IMC to growth. At the same time, the rate of cooling has a remarkable effect on the morphology of size of Ag3Sn which evolved into large plate-like shapes with decreasing rate of cooling.